1986
DOI: 10.1266/jjg.61.419
|View full text |Cite
|
Sign up to set email alerts
|

Rates of flagellar- and P1 infective-phase variation by three site-specific recombinase genes in every possible combination.

Abstract: Rates of flagellar-and P1 infective-phase variation, caused by reversible inversion of an H(=PD) and a C segment, respectively, were examined with strains having the three site-specific recombinase genes, hin+, pin+, and cin+, in every possible combination. The variation rates were compared in terms of gene functions on the assumptions that the three genes are similar in gene dosage and comparable with one another in the amount of gene products and that each rate reflects an activity of a single gene or genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…X-Gal plates contained 40 mg of 5-bromo-4-chloro-3-indolyl-3-D-galactosidase (Sigma) per liter. Anti-flagellum serum against an e,n,x antigen was as previously described (31 (51) were deleted stepwise in opposite directions by using exonuclease III and mung-bean nuclease (Takara), and a series of deletion plasmids was used for sequencing. Nucleotide and amino acid sequences were analyzed by using DNASIS sequence analysis software (Hitachi Software Engineering Co.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…X-Gal plates contained 40 mg of 5-bromo-4-chloro-3-indolyl-3-D-galactosidase (Sigma) per liter. Anti-flagellum serum against an e,n,x antigen was as previously described (31 (51) were deleted stepwise in opposite directions by using exonuclease III and mung-bean nuclease (Takara), and a series of deletion plasmids was used for sequencing. Nucleotide and amino acid sequences were analyzed by using DNASIS sequence analysis software (Hitachi Software Engineering Co.).…”
Section: Methodsmentioning
confidence: 99%
“…Since the rate from C(-) to C(+) by the cin gene has been reported to be 3.4 x 10-2 (31), it was determined that S. boydii and S. dysenteriae can mediate C inversion with frequencies three orders and one order of magnitude lower than that of the cin gene, respectively. A similar experiment was performed with S. sonnei, since our earlier study had suggested that this strain can mediate C inversion (48).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic change caused by P inversion is unknown. In contrast to the difference in biological function, these recombinases are functionally interchangeable with one another (Kamp & Kahmann, 1981; Kutsukake & Iino, 1980; Momota & Enomoto, 1986; van de Putte et al ., 1984).…”
Section: Introductionmentioning
confidence: 99%